Síndrome de Bartter como causa de atraso no crescimento e de surdez neurossensorial - Lorena Lago de Menezes; Luísa Lemos Pimentel; Lavinia Lago de Menezes; Diego Augusto Alves Rosa; Maylon Rudney de Sousa Ferreira (Sociedade Brasileira de Pediatria, 2023)
Bartter syndrome (BS) is a rare renal tubulopathy, which typically becomes apparent during childhood. It is caused by an autosomal recessive inheritance which involves the kidneys' ability to reabsorb sodium. This report depicts a case of an 18 month-old patient with several manifestations suggesting BS, such as hypokalemia, hypercalciuria, metabolic alkalosis, polyuria, polydipsia, growth delay and congenital bilateral sensorineural hearing loss. The diagnosis was confirmed after a genetic test by classifying the patient as type IV BS. In this context, knowing about BS is crucial to include it in the differential diagnosis of early onset tubulopathies. Therefore, the possible impacts of this condition can be minimized, leading to a better quality of life for the affected.